An Update on Lower Lid Blepharoplasty - Murri, Michael; Hamill, Eric B.; Hauck, Matthew J.; Marx, Douglas P. (Seminars in Plastic Surgery, 2017)
Aging changes to the lower eyelids and midface include pseudoherniated orbital fat, tear trough deformity, lid laxity, and dermatochalasis. Surgical repair often aims at treating redundant skin or orbital fat malposition with a lower eyelid blepharoplasty. Either a transcutaneous or transconjunctival approach may be used, though recent trends have favored the transconjunctival technique if procedures require more than simple skin excision. In manipulating the inferior orbital fat pads, a surgeon has many options including excision, repositioning, or augmentation with synthetic dermal filler, autologous fat grafts, or acellular dermal allografts. The authors review and detail indications, preoperative evaluation, techniques, and complications of lower lid blepharoplasty.
Keywords: lower lid blepharoplasty; infraorbital fat; tear trough deformity